PENGARUH KONSENTRASI LARUTAN LFC-12 SEBAGAI EDIBLE COATING DAN LAMA PENYIMPANAN TERHADAP SIFAT FISIKOKIMIA FLAKE BERAS HITAM (ORYZA SATIVA L. INDICA) - Soebroto, Janice Utami; Suseno, Thomas Indarto Putut; Widoeri, Theresia Endang (Widya Mandala Surabaya Catholic University, 2012)
Black rice (Oryza sativa L. indica) is a local variety that contains anthocyanin so the grains have a dense purple color approaching black. Black rice has 74.81% carbohydrates as a major component so that can be applied to flake form as a practicable breakfast menu. However, that application can reduce anthocyanin in black rice. Therefore, it leads the idea to use L-FC12 solution as edible coating in black rice. This research aims to determine the effect of L-FC12 concentration and storage time on the physicochemical properties of black rice flake. Design research is Nested RCBD (Randomized Completely Block Design) with double factor consisting of the L-FC12 solution concentrations (0%, 20%, 40%, 60% and 80%) and the storage time (0, 20 and 40 days) as the nested factor with three replications. Parameters observed include color, rehydration, water content and anthocyanin. Data are to be analyzed using analysis of variance (ANOVA) at α = 5%. If the result of ANOVA shows significant effect prevails, Duncan's Multiple Range Test shall be done at α = 5% to show the difference among treatments. The best treatment is determined by additive weighting and non-dimensional scaling. Differences in L-FC12 concentration cause equal effects on water content (8,04 % - 10,69 %) and anthocyanin content (97,494 mg/g –292,482 mg/g), opposite effect on rehydration (59,00 % – 127,33 %), but no effects on lightness, redness and yellowness black rice flake. While the storage time cause equal effect on water content and lightness, cause opposite effect on anthocyanin content and rehydration. Storage time cause the fluctuations of redness and yellowness.